Lymph node metastases outside tumor-bearing lobes and/or segments in non–small cell lung cancer - Han, Lu; Jia, Hui; Song, Pingping; Liu, Xibin; Wang, Zhendan; Zhang, Dujian (Frontiers in Medicine, 2022)
Objective Hilar and lung lymph node metastases (N1) are defined as ipsilateral bronchial and intrapulmonary lymph nodes. However, the cleaning standards for ipsilateral bronchial lymph nodes in different lobes and segments within the same lobe in segmentectomy are not clearly defined. Method: Sixty-six patients undergoing pulmonary resection for the treatment of lung cancer were evaluated. Intraoperatively visible non-tumor-bearing lobe (NTBL) and postoperatively non-tumor-bearing segment (NTBS) lymph nodes were removed and analyzed. The associations between the NTBL LNs and clinicopathological characteristics were analyzed. Results: NTBL LNs metastases were found in 8 (12.1％) of the 66 patients, NTBS LNs metastasis were not found(0/13). The presence of NTBL metastases was significantly associated with age (＜60 years vs .≥ 60 years, P = 0.037), differentiation（Grade 1 well differentiated vs. Grade 2 moderately differentiated vs. Grade 3 poorly differentiated, P =0.012), cN2 (node-positive vs. node-negative, P =0.022), pN stage (N0 vs. N1 vs. N2, P =0.003) and p stage (Ⅰvs.Ⅱ vs. Ⅲ, P =0.009). Multivariate logistic analysis showed that tumor differentiation (P = 0.048, HR 6.229; 95% CI 1.016-38.181) and pN (P = 0.024, HR 5.099; 95% CI 1.245-20.878) were statistically significant predictors. Conclusions: The dissection of NTBL is necessary not only to reduce the local recurrence rate but also to predict patient prognosis. Although lymph node metastases in NTBS are rare, further investigation of the need to dissect is required.